Practical course on spelling and literary editing: practical course - Odekova F. R. (Ставрополь, СКФУ, 2023)
The workshop is made according to requirements of VO NCFU OS and contains practical tasks and exercises. It is intended for the students studying in the direction of preparation 45.03.01 Philology, to orientation (profile) “Domestic philology”